The first complete mitochondrial genome of Dermestes vorax (Coleoptera: Bostrichiformia: Dermestidae) from China and its phylogenetic analyses - Changping Ding; Jian Shen; Shuoying Ning; Meixia Yang (Mitochondrial DNA. Part B. Resources)
Dermestes vorax is a significant storage pest which challenging to distinguish it from Dermestes lardarius by external morphological characteristics. This study presents the complete mitochondrial genome of D. vorax. The mitogenome of D. vorax spans 15,775 bp and comprises 13 protein-coding genes (PCGs), 22 tRNA genes, two rRNA genes, and an AT-rich region. The nucleotide composition includes A (41.51%), C (14.14%), G (9.03%), and T (35.32%). Phylogenetic analyses by Bayesian inference and maximum-likelihood methods suggest the relationship among three subfamilies: Dermestinae + (Attageninae + Megatominae). Additionally, phylogenetic analysis indicates that D. vorax is more closely rated to D. lardarius.